Beyond methodology : feminist scholarship as lived research - Cook, Judith A.; Fonow, Mary Margaret (US : Indiana University Press, 1991)
Back to the Future: a look at the second wave of feminist epistemology and methodology--The man of professional wisdom--Learning from the outsider within: the sociological significance of black feminist thought--Women's resarch or feminist research? the debate surrounding feminist science and methodology--Quantitative and qualitative methods in the social sciences--Race and class bias in qualitative research on women--Researching the women's movement...
Keywords: FEMINISMO; EPISTEMOLOGIA; CIENCIAS SOCIALES